2019
DOI: 10.7454/mst.v23i1.3643
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Properties of A Novel Solid Biopolymer Electrolyte based on Algi-nate Incorporated with Citric Acid

Abstract: In the present study, a novel solid biopolymer electrolyte (SBE) system is introduced by doping citric acid into alginate polymer. A sample of the alginate-citric acid SBE system was prepared via a solution casting technique. Using electrical impedance spectroscopy (EIS), the electrolytes of alginate-citric acid analyzed from 5 Hz to 1 MHz achieved the highest conductivity at 20 wt.% of 5.49 × 10 -7 S cm -1 . The temperature dependence of various citric acid amounts obeyed the Arrhenius rule with R 2~1 , where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…reported 1.80 V for Alginate with LiBr. [ 20 ] For Tamarind seed polysaccharide doped with Magnesium perchlorate possess the electrochemical stability is 2.85 V reported by Perumal et al. and 3.58 V for Cellulose acetate doped with Magnesium per chlorate reported by Mahalakshmi et al.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…reported 1.80 V for Alginate with LiBr. [ 20 ] For Tamarind seed polysaccharide doped with Magnesium perchlorate possess the electrochemical stability is 2.85 V reported by Perumal et al. and 3.58 V for Cellulose acetate doped with Magnesium per chlorate reported by Mahalakshmi et al.…”
Section: Resultsmentioning
confidence: 94%
“…Infanta Diana et al have described the electrochemical stability value of Sodium alginate with Sodiumthocyanide (NaSCN) polymer electrolyte has 2.7 V. [26] Fuzlin et al reported 1.80 V for Alginate with LiBr. [20] For Tamarind seed polysaccharide doped with Magnesium per- chlorate possess the electrochemical stability is 2.85 V reported by Perumal et al and 3.58 V for Cellulose acetate doped with Magnesium per chlorate reported by Mahalakshmi et al [15,27]…”
Section: Linear Sweep Voltammetrymentioning
confidence: 89%
“…Moreover, both dielectric constant and dielectric loss were drastically decreasing when frequency was increased. This situation can be explained due to rapid reversal process of electric field gives less or no time for the mobile ions to diffuse and migrate, indicated a non-Debye behaviour with no single relaxation time [17]. The constant value of dielectric permittivity at high frequency is believed due to periodic reversal of the field occurring so quickly that the charge carriers were distressed to orient themselves in the field direction, in turn leading to a decrement in the dielectric constant and dielectric loss [16].…”
Section: Fig 1 Cole-cole Plot Of Sbe At Selected Ec Compositionmentioning
confidence: 99%
“…It revealed that both the dielectric constant and dielectric loss increases with increasing in temperature. This phenomenon can be described as the temperature increases, the degree of GA dissociation to released H + and hoping to alginate polymer has increased thus lead to the increment of ionic conductivity at higher temperature [14,15]. A further investigation of the dielectric behavior can be more successfully achieved using an electrical modulus study that suppresses the effect of electrode polarization.…”
Section: Industrial Science and Technologymentioning
confidence: 99%